2017
DOI: 10.1002/jsfa.8380
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high‐fat diet and growth stage on the diversity and composition of intestinal microbiota in healthy bovine livestock

Abstract: The 6-month cattle and female parents shared similar intestinal bacteria; the community structure of fecal microbiota was significantly affected by high-fat diet in older cattle. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Similar to the abovementioned cysteine, methionine is crucial in maintaining the functions of intestinal cells by regulating the redox status (Azad et al, 2019). Thus, enhanced methionine metabolism in the gut microbial communities contributed to bovine body weight gain (Jiao et al, 2017). On the other hand, ABC transporters involved in transporting a large variety of sterols, lipids, drugs, and primary and secondary metabolites (Hou et al, 2017) have recently been related to fat deposition, drug resistance, and colonic inflammation (Andersen et al, 2015;Fang et al, 2017), which may do harm for growth performances in animals.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the abovementioned cysteine, methionine is crucial in maintaining the functions of intestinal cells by regulating the redox status (Azad et al, 2019). Thus, enhanced methionine metabolism in the gut microbial communities contributed to bovine body weight gain (Jiao et al, 2017). On the other hand, ABC transporters involved in transporting a large variety of sterols, lipids, drugs, and primary and secondary metabolites (Hou et al, 2017) have recently been related to fat deposition, drug resistance, and colonic inflammation (Andersen et al, 2015;Fang et al, 2017), which may do harm for growth performances in animals.…”
Section: Discussionmentioning
confidence: 99%
“…The important effects of gut microbial amino acid and butanoate metabolism on animals’ production performance have been demonstrated in earlier studies. Jiao et al indicated that cysteine and methionine metabolism mediated by gut microbiota significantly affects average daily gain of young cattle (Jiao, et al , ). Guevarra, et al () reported that gut microbiota involved in arginine and proline metabolism could alleviate weaning stress and improve growth performance in piglet.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, rumen protozoa and anaerobic fungi tend to have lower concentrations in high grain-fed animals, but not always (e.g., cows with diet-induced ruminal acidosis can have a higher abundance of rumen fungi than healthy cows) [ 98 ], while the starch-degrading Entodinium becomes dominant in high grain diets [ 101 ]. Microbiota composition is also affected by feed supplements [ 145 , 146 ], periodical starvation [ 147 ] and high fat diets [ 148 ].…”
Section: Stec Emergence In Cattle Farmsmentioning
confidence: 99%